NAS FRONTEIRAS: O HINDU-CRISTIANISMO DE BEDE GRIFFITHS - Thomaz, Angelica Tostes (2019)
This research aims at describing Father Bede Griffiths’s (1906-1993) inter-religious experience and analysing his work on the hindu-christian dialogue according to his view. His experience is understood from a post-colonial perspective on social studies and the concepts of “borders”, “inbetweenness!” and margins as proposed by Homi Bhabha. Griffiths’s life has allowed new paths to the inter-religious discourse. The hindu-christian dialogue built so far will be analysed and search for new post-colonial horizons. This article also aims at showing how his experience was meaninful to the hindu-christian interreligious dialogue and achieving new possibilities through Grif- fiths’s experience.